Appropriate for Use Under Advanced Manu Facturing Technology: An Application in Baghdad Soft Drinks Company " Private Contribution (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Big developments in technology have led to upset the balance of ideas, given of its own post new properties for products not provided by traditional technology, especially economic units operating within the industrial sector, and therefore it is important to develop the Iraqi industrial sector and interest to do its vital role in light Of progress technological.The research aims to Find the use of advanced manufacturing technologies that lead to customized production and quality appropriate whether they are low quality and low cost or low cost and suitable quality or high quality and high cost to win customer satisfaction.While the important conclusions is that the application of advanced manufacturing technology is not limited to technological change, but there must be a change on the economic unit level representatives of the workers and convince them to accept and support the change, because the benefits can’t be acquired in full only if there is consistency between the unit and technology. And conclude research necessity to take advantage of other Iraqi industrial companies from the experience of Baghdad Company for soft drinks as it is alone present time using advanced manufacturing technology for the betterment of the industrial reality serve the national economy.